Assessment of the efficiency of the integrated application of educational software when teaching children with mild intellectual disabilities (MID) - Pantelis, Efstratios; Tsankov, Nikolay (Special Education, 2017)
Learning software for children with intellectual disabilities is particularly important because some of the solutions are highly practical, allowing for easy presentation of different types of incentives and goals, often with higher quality than other media. Educational information and communication technologies, and in particular the various software packages, provide a wider range of incentives for pupils with mild intellectual disability and create a favorable environment for their full development in different areas through a list of activities that ensure progress. This study presents an evaluation of performance results from the use of specially selected software products in the education of children with mild intellectual disabilities. This is an attempt to prove the hypothesis that the systematic and targeted application of information and communication technologies, and in particular specific software products (such as "AKTINES", "I learn to run with security", "Small works in action", "STERXIS", "Round with value" and "My home and school “) improves the efficiency of the educational process.